Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea - Motomura, Hiroyuki; Last, Peter R.; Yearsley, Gordon K. (Zootaxa, 2005)
A new species of small-sized scorpionfish, Scorpaena bulacephala, is described on the basis of seven specimens collected from off Norfolk and Lord Howe Islands, northern Tasman Sea, southwestern Pacific Ocean, at depths of 86–113 m. The new species is closely related to a Hawaiian endemic species, S. colorata. The two species are distinguished from other Indo–Pacific species of Scorpaena by the following combination of characters: exposed cycloid scales covering the anteroventral surface of the body and pectoral-fin base, the lateral surface of the lacrimal without spines, and 17 pectoral-fin rays. The new species differs from S. colorata in having 39–44 longitudinal scales rows and relatively short fin spines and rays, especially short longest pectoral-fin ray (31.5–33.5% of standard length). Morphological changes with growth and sexual dimorphism of the new species are also discussed.